Direct measurement of transversely isotropic DNA nanotube by force–distance curve‐based atomic force microscopy. (1st October 2015) - Ma, Zhipeng; Kim, Young‐Joo; Park, Seongsu; Hirai, Yoshikazu; Tsuchiya, Toshiyuki; Kim, Do‐Nyun; Tabata, Osamu
Abstract : DNA origami is one of the most promising ways to create novel two‐dimensional (2D) and 3D structures, assemble inorganic and organic materials, and synthesise functional micro/nano systems. In particular, DNA origami structures consisting of nanotube configurations can function as mechanical components for encapsulating materials such as gold particles or drug proteins, due to their tubular structure, relatively high rigidity, high aspect ratio and other desirable characteristics, but certain mechanical properties such as radial rigidity have yet to be fully determined experimentally. A report is presented on the direct measurement of the radial modulus of a DNA nanotube structure by force–distance curve‐based atomic force microscopy, in a magnesium ion solution. A Hertz model, corrected using the finite‐element method to achieve greater realism, was employed to determine the DNA nanotube's actual radial modulus in two states, corresponding to the rigidity of a porous and electrostatically repulsive nanotube lattice, and the rigidity of a packed and elastic honeycomb lattice. Furthermore, the biphasic radial modulus was verified by estimation of the inter‐helix electrostatic force and torsional rigidity of a six‐helix DNA nanotube, with results comparable to those reported elsewhere. The anisotropy of the DNA nanotube honeycomb lattice revealed by the authors' radial measurements should be useful when developing new DNA structures and may enable further applications that utilise DNA origami structures as a mechanical component.